Pemetaan Kasus DBD di Pulau Lombok menggunakan Regresi Binomial Negatif berbasis Geografis - Ayundasari, Dita Septiana; Hastuti, Siti Hariati; Kertanah, Kertanah (Universitas Hamzanwadi, 2024)
According to the Indonesia Health Profile Report 2022, NTB Province is among the 11 provinces with the highest incidence rate of dengue hemorrhagic fever (DHF). On Lombok Island, there were 2,074 cases with 4 deaths in 2022. DHF remains a serious threat in Lombok, so this study aims to map sub-districts based on significant factors for the spread of DHF in 54 sub-districts throughout Lombok Island. This study used quantitative analysis with one response variable, the number of DHF cases, and three predictor variables: the ratio of medical personnel (nurses) (X1), the percentage of proper sanitation facilities (healthy latrines) (X2) and the percentage of standard drinking water facilities (X3) in 54 sub-districts. Data were obtained from the Health Office throughout Lombok Island. Analysis techniques include descriptive analysis, GWNBR modeling, and significant variable mapping. The mapping results showed six groups of sub-districts with a combination of significant variables, which included variables X1, X2, and X3. The findings suggest the need for additional studies or prevention policies that are more focused on hygiene to reduce the risk of DHF spread. Related parties also need to be informed to take strategic steps based on these findings.